Effect of the conventional and organic fertilization on fruiting efficiency and on evolution of the edaphic macrofauna in banana cultivars. - Patiño, Marcelo (2017)
This study was designed to evaluate the effect of inorganic and organic fertilizers on banana fruiting, as well as its effect on edaphic macro fauna in banana cultivars in Ecuador. In this study, Dwarf Curaré variety meristematic banana plants were used with different inorganic fertilizers included: CH 4 N 2 O, KCl, (NH 4) 2 HPO 4 , CaH 4P2O8 , K, Mg. Organic solid fertilizers were used as a counterpart. The treatments used to be: (T1) without nitrogen fertilization; (T2) 60; (T3) 120; (T4) 180; (T5) with 240 kg ha-1 of N respectively; (T6, T7, T8) with 1, 2 and 3 kg of organic solid fertilizer per plant1; (T9) mix of T3+T6; (T10) mix of T2+T7. It was found that the application of nitrogen reduced the flowering time by 35 days. Also, it was noted that the use of organic nitrogen did not have the same effect as inorganic nitrogen on fruiting and finally nitrogen accumulation in bunches and fruits. The application of organic and inorganic fertilizers, did not affect the biomass of organisms in the soil